Anatomical Atlas of the Quail's Ear (Coturnix coturnix). (22nd September 2015) - Bonsmann, A.; Stoffel, M. H.; Burkhart, M.; Hatt, J.‐M.
Summary: This study aims to enhance the anatomical knowledge of the ear of the adult quail ( Coturnix coturnix ) through the creation of a scaled 3D model utilizing data from micro‐CT images. In addition, 17 annotated histological sections of the quail's ear are aligned to their 3D position in the model. The resulting anatomical atlas provides an intuitive insight into the 3D anatomy and can be used for medical education. The model also allows measuring anatomical structures and can thus serve as reference for the quail's auricular anatomy and as a basis to evaluate clinical diagnostic imaging results.